Laparoscopic double cholecystectomy for biliary dyskinesia in a child with duplicated gallbladders - Jose L. Diaz-Miron; R. Elliott Overman; Shaun M. Kunisaki (Elsevier, 2019)
Gallbladder duplication is an uncommon congenital anomaly with an estimated incidence of 1 in 4000 patients. Here we present a child who underwent a duodenal duplication cyst marsupialization who continued experiencing chronic abdominal pain one year after the initial procedure. She had an incidentally discovered duplicated gallbladder on ultrasound and an ejection fraction of 2% on hepatobiliary iminodiacetic acid (HIDA) scanning. Preoperative magnetic resonance cholangiopancreatography (MRCP) revealed two gallbladders with individual cystic ducts. She underwent an uneventful laparoscopic double cholecystectomy for biliary dyskinesia and subsequently had resolution of her chronic abdominal pain. Keywords: Duplicated gallbladder, Biliary dyskinesia, Pediatric, Cholecystectomy, Duodenal duplication